Dissociable Roles of Cerebral mu-Opioid and Type 2 Dopamine Receptors in Vicarious Pain: A Combined PET-fMRI Study - Karjalainen T; Karlsson HK; Lahnakoski JM; Glerean E; Nuutila P; Jaaskelainen IP; Hari R; Sams M; Nummenmaa L (OXFORD UNIV PRESS INC, 2025)
Neuroimaging studies have shown that seeing others in pain activates brain regions that are involved in first-hand pain, suggesting that shared neuromolecular pathways support processing of first-hand and vicarious pain. We tested whether the dopamine and opioid neurotransmitter systems involved in nociceptive processing also contribute to vicarious pain experience. We used in vivo positron emission tomography to quantify type 2 dopamine and mu-opioid receptor (D2R and MOR, respectively) availabilities in brains of 35 subjects. During functional magnetic resonance imaging, the subjects watched short movie clips depicting persons in painful and painless situations. Painful scenes activated pain-responsive brain regions including anterior insulae, thalamus and secondary somatosensory cortices, as well as posterior superior temporal sulci. MOR availability correlated negatively with the haemodynamic responses during painful scenes in anterior and posterior insulae, thalamus, secondary and primary somatosensory cortices, primary motor cortex, and superior temporal sulci. MOR availability correlated positively with orbitofrontal haemodynamic responses during painful scenes. D2R availability was not correlated with the haemodynamic responses in any brain region. These results suggest that the opioid system contributes to neural processing of vicarious pain, and that interindividual differences in opioidergic system could explain why some individuals react more strongly than others to seeing pain.